Life lines : writing transcultural adoption - McLeod, John, 1969- (New horizons in contemporary writing., 2015)
"Adoptions that cross the lines of culture, race and nation are a major consequence of conflicts around the globe, yet their histories and representations have rarely been considered. Life Lines: Writing Transcultural Adoption is the first critical study to explore narratives of transcultural adoption from contemporary Britain, Ireland and America: fictions, films and memoirs made by those within the adoption 'triad' or those concerned with the pain and possibilities of transcultural adoption. While acknowledging the sobering inequalities which engender transcultural adoptions and the lasting upset of sundered relations, at the same time John McLeod considers the transfigurative and creative propensity of imagining transcultural adoption as radically calling into question ideas of biogenetic attachment, racial genealogy, cultural identity and normative family-making. How might the predicament of 'being adopted' transculturally enable the transformative agency of 'adoptive being' for all? Exploring works by Andrea Levy, Barbara Kingsolver, Toni Morrison, Sebastian Barry, Caryl Phillips, Jackie Kay and several others, Life Lines makes a groundbreaking intervention in such fields as transcultural studies, postcolonial thought, and adoption theory and practice."--Bloomsbury Publishing